Pharmacotherapy of Hospitalized Patients with COVID-19 at a Tertiary Care Hospital in Nepal - Mudvari, Dr Anish; Prasad, Pravin; Pokharel, Akritee; Thapaliya, Sabin; Maharjan, Bindira; Khadka, Rebanta; Lamsal, Arun Batsa; Ghimire, Ranjeet; Bista, Apeksha (Journal of Institute of Medicine Nepal, 2025)
Introduction: The global COVID-19 pandemic has posed a significant health threat due to the high transmission rates and lack of standardised treatments. Multiple therapeutic agents, including antivirals, antibacterial, and immunomodulators, have been used, but there are no established treatments specifically targeting SARS-CoV-2. This study aims to assess the trend of the pharmacotherapy used in COVID-19 patients admitted to a tertiary care during the second wave of the pandemic. Methodology: A retrospective, observational, cross-sectional study was conducted in a tertiary care centre, utilising patient data from April 2021 to July 2021. The sample included 310 patients admitted with a confirmed diagnosis of COVID-19. Patients were classified based on oxygen requirement levels, and data were analysed using descriptive statistics. Results: Of the 310 patients, 59% were male and 41% female, with a mean age of 53.37 ± 17.01 years. The average hospital stay was 10 ± 7.15 days. Most patients (66.8%) required supplemental oxygen, and 7.4% required mechanical ventilation. The majority received antimicrobial therapy, with ceftriaxone being the most commonly prescribed antibiotic (73.22%). Remdesivir was the predominant antiviral, and dexamethasone was used in 88.39% of patients. Conclusion: Antibiotic use was extensive among hospitalised COVID-19 patients, with ceftriaxone being the most common. Antiviral use was less frequent, with Remdesivir being the preferred choice. Dexamethasone played a crucial role in managing severe cases.